-5(4x-2)=-4(1-6x)

Simple and best practice solution for -5(4x-2)=-4(1-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(4x-2)=-4(1-6x) equation:



-5(4x-2)=-4(1-6x)
We move all terms to the left:
-5(4x-2)-(-4(1-6x))=0
We add all the numbers together, and all the variables
-5(4x-2)-(-4(-6x+1))=0
We multiply parentheses
-20x-(-4(-6x+1))+10=0
We calculate terms in parentheses: -(-4(-6x+1)), so:
-4(-6x+1)
We multiply parentheses
24x-4
Back to the equation:
-(24x-4)
We get rid of parentheses
-20x-24x+4+10=0
We add all the numbers together, and all the variables
-44x+14=0
We move all terms containing x to the left, all other terms to the right
-44x=-14
x=-14/-44
x=7/22

See similar equations:

| u+7/u+3=u+7/u+4+1 | | 15x(7-7)+(5x2)=10 | | 0=2(x^2+2x-600) | | 4-5(x-2)=2/3(3x+12) | | 6-6(p+2)=3p-6(6p-8) | | 6–3*x=4*(3–x)–6 | | -3/7v+3=33/7 | | 7x-5=7x-8 | | 4x=6=70 | | 3h=10.74 | | 176=-4(-5a-4) | | 6x+8x-4=5(2x+5+1 | | 4x^2=6=70 | | 12=x/9-17 | | -1/3m+6=12 | | 85=-5(2v-7) | | 17=d+3 | | 0.2(x+6)=0.33(x-6) | | -4(6+8p)=104 | | 12=x9−1712=x9-17 | | 3x+18=-6x+12 | | 8x-6=6x-18 | | y-(35/100)y=65 | | 0=9*x^2-60*x+64 | | 7x+6=104 | | 3+4p=5p+4 | | y-(35/100y)=65 | | 1/5(x+6)=1/3(x-6) | | 100x+45=347.50 | | v−1.06=1.84 | | b+5.3=6.5 | | 25+150x=55x |

Equations solver categories